STRATEGI PEMANFAATAN SUMBERDAYA IKAN SID AT, Anguilla spp. DI INDONESIA [Strategy on Utilization of Eel (,Anguilla sp.) Resources in Indonesia] - Ridwan Affandi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Indonesia has a high potency of eel resources but their utilization has been very limited. For increasing their utilization, we need strategic steps. First step, is an effort to recognize the location, where eel resources potency and then mapping their potency. Second step, is an effort to increase eel utilization for local consumption by intensive promotion, and third step is to increase eel culture activity.